Dissent on core beliefs: religious and secular perspectives - Chambers, Simone; Nosco, Peter (Cambridge books online, 2015)
Difference, diversity and disagreement are inevitable features of our ethical, social and political landscape. This collection of new essays investigates the ways that various ethical and religious traditions have dealt with intramural dissent; the volume covers nine separate traditions: Confucianism, Buddhism, Christianity, Judaism, Islam, liberalism, Marxism, South Asian religions and natural law. Each chapter lays out the distinctive features, history and challenges of intramural dissent within each tradition, enabling readers to identify similarities and differences between traditions. The book concludes with an Afterword by Michael Walzer, offering a synoptic overview of the challenge of intramural dissent and the responses to that challenge. Committed to dialogue across cultures and traditions, the collection begins that dialogue with the common challenges facing all traditions: how to maintain cohesion and core values in the face of pluralism, and how to do this in a way that is consistent with the internal ethical principles of the traditions